2021
DOI: 10.33369/pendipa.5.3.403-411
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Self-Directed Learning (SDL) dalam Pembelajaran Fisika SMA Berbasis Daring Pada Pokok Bhasan Hukum Newton

Abstract: Currently, all Indonesian regions are experiencing a severe pandemic condition that affected all fields, including the education sector. The education system that is usually face-to-face has to turn online, which forces students with teaching staff to carry out the learning process from home. With online-based learning, teachers and students can take advantage of online learning-based platforms, like Google Classroom, to implement Self-Directed Learning (SDL), where there are adjustments to learning devices an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
5
Order By: Relevance
“…Then research conducted by (Saputra, 2021) found that student self-directed learning readiness is still at a moderate stage, so it is necessary to identify students' independent learning needs and develop a complete online learning schedule. Then another study also found that the application of SDL was able to improve students' cognitive abilities in online-based physics learning for Newton's Law material (Permatasari & Anggaryani, 2021).…”
Section: Students Are Given Feedback From the Teacher Post Activity -mentioning
confidence: 94%
See 1 more Smart Citation
“…Then research conducted by (Saputra, 2021) found that student self-directed learning readiness is still at a moderate stage, so it is necessary to identify students' independent learning needs and develop a complete online learning schedule. Then another study also found that the application of SDL was able to improve students' cognitive abilities in online-based physics learning for Newton's Law material (Permatasari & Anggaryani, 2021).…”
Section: Students Are Given Feedback From the Teacher Post Activity -mentioning
confidence: 94%
“…Research conducted by (Saputra, 2021) found that students' selfdirected learning readiness is still at a moderate stage, so it is necessary to identify students' independent learning needs and develop a complete online learning schedule. Another study also found that the application of SDL was able to improve students' cognitive abilities in online-based physics learning for Newton's Law material (Permatasari & Anggaryani, 2021). The purpose of this study was to analyze the perception of English teachers about independent learning, describe the activities provided by the teacher in online learning, and identify the components of independent learning that can be identified in online learning activities.…”
Section: Introductionmentioning
confidence: 99%
“…Model SDL terhadap hasil belajar (Permatasari & Anggaryani, 2021) SDL dapat dilakukan secara praktis dan dikategorikan sangat baik (Amaliyah et al, 2019) Siswa SDL memiliki pencapaian kemampuan lebih baik dibanding siswa yang tidak menerapkan SDL (Zamnah & Ruswana, 2018) Perbedaan peningkatan kemampuan pemahaman matematis mahasiswa SDL dengan yang tidak menerapkan SDL (Istiyani, 2009) Self -directed learning sebagai salah satu alternatif pembelajaran.…”
Section: Peneliti Dan Tahununclassified
“…Dalam pembelajaran mandiri siswa perlu memiliki self regulated learning atau kemandirian belajar. Kemandirian belajar dapat membantu Adapun pertanyaan pertama mengenai pengaruh model self-directed learning terhadap hasil pembelajaran yaitu SDL dapat dilakukan secara praktis dan dikategorikan sangat baik (Permatasari & Anggaryani, 2021), Siswa SDL memiliki pencapaian kemampuan lebih baik dibanding siswa yang tidak menerapkan SDL (Amaliyah et al, 2019), Perbedaan peningkatan kemampuan pemahaman matematis mahasiswa SDL dengan yang tidak menerapkan SDL (Zamnah & Ruswana, 2018), Self -directed learning sebagai salah satu alternatif pembelajaran (Istiyani, 2009).…”
Section: Tabel 3 Model Pembelajaran Yang Mampu Meningkatkan Kemampuan...unclassified
“…Penelitian sebelumnya mengkonfirmasi bahwa penerapan SDL dalam pembelajaran dapat memfasilitasi siswa untuk membangun kemandirian belajar siswa (Rifanti & Pujiharsono, 2018). Selain itu, model SDL merupakan model pembelajaran yang dapat diterapkan untuk meningkatkan pencapaian pembelajaran serta prestasi belajar siswa (Permatasari & Anggaryani, 2021). Penerapan pembelajaran SDL pada mata pelajaran fisika dapat memfasilitasi siswa untuk meningkatkan kemampuan kognitif yang berhubungan dengan penguasaan konsep serta penerapannya dalam kehidupan sehari-hari (Handayani, 2017).…”
unclassified